Utilización de Instagram, Facebook y WhatsApp en las empresas de Delivery en la ciudad de Machala durante la pandemia. - Eras Valverde, Dixi Mireya; Matute Quito, Mirian Alexandra (My University, 2021)
Human behavior has evolved rapidly due to technological changes. Social platforms have become a way for the entrepreneur and his clients to communicate, However, many entrepreneurs do not use this tool well. The purpose of this research is to analyze the presence of social networks in delivery companies in the city of Machala. The methodology used is qualitative kind, which includes a brief bibliographic review based on scientific articles about social networks and delivery companies. After that, delivery companies are searched on social networks and observation is made. After-wards, interviews are conducted with entrepreneurs who have a greater presence on social networks. Finally, the information collected was verified using a focus group made up of 6 clients that make use of the delivery service. The results reflected that delivery entrepreneurs use social networks superficially, and they don't do it as a po-tential source of income. It is evident the lack of knowledge and the little interest that the entrepreneur puts on social networks.
El comportamiento del ser humano ha evolucionado de forma acelerada debido a los cambios tecnológicos. Las plataformas sociales se han convertido en una vía donde se puede comunicar el empresario y sus clientes, sin embargo, muchos empresarios no utilizan bien esta herramienta. El propósito de esta investigación es analizar la presencia de las redes sociales en las empresas de delivery en la ciudad de Machala. La metodología utilizada es de tipo cualitativa, que incluye una breve revisión bibliográfica en base a artículos científicos sobre las redes sociales y las empresas de delivery. Posterior a eso, se busca empresas de delivery en redes sociales y se realiza la observación. Después, se realiza entrevistas a empresarios que tienen mayor presencia en las redes sociales. Finalmente, se comprobó la información recopilada utilizando un grupo focal conformado por 6 clientes que hacen uso del servicio de delivery. Los resultados reflejaron que los empresarios de delivery usan las redes sociales de manera superficial, y no lo hacen como una fuente de ingreso potencial. Es evidente la falta de conocimiento y el poco interés que el empresario le pone a las redes sociales.
Keywords: REDES SOCIALES; DELIVERY; CLIENTE